Silício poroso para aplicações em sensores e microssistemas. - Galeazzo, Elisabete (2000)
Photoluminescent porous silicon (PS) is a promise material for optoelectronic applications. Due to its high surface area and chemical reactive characteristic can be utilised as sensor material, and, through porous silicon formation on selective areas, as sacrificial material for fabrication of microelectromecanism. This work presents the obtention of PS monolayers and multilayers characterised structurally by gravimetric technique, Raman spectroscopy, scanning electron microscopy andatomic force microscopy. Alterations of surface chemical bonds are analysed by Fourier transform infrared (FTIR) due the ageing process and chemical treatments. The evolution of photoluminescence is correlationed with FTIR measurements with the aim to contribute on clearing up about PS light emission basic mechanism. The alterations of electrical properties of the oxidised PS devices, submitted to saturated environment with polar and apolar molecules are characterised through impedance and capacitance measure. The PS electrical conduction mechanism is related with charge carrier transport through localised states on PS surface. Selective PS formation during anodization was implemented by mean of thick silicon oxide deposition and hydrogen ion implantation processes. The thick silicon oxide deposited by plasma enhanced chemical vapour deposition \"PECVD\" limits the anodization time and induces stress between the interface of oxide and Si. The hydrogen ion implantationassociated with adequate annealing was utilised for the first time with the intuit to block the anodization. PS selective and isotropic layers were obtained with this technique.